Genomic Profile and BRCA-1 Promoter Methylation Status in BRCA Mutated Ovarian Cancer: New Insights in Predictive Biomarkers of Olaparib Response - Franzese, Elisena; Centonze, Sara; Diana, Anna; Lombardi, Angela; Carlino, Francesca; Guerrera, Luigi Pio; De Vita, Ferdinando; Caraglia, Michele; Pignata, Sandro; Ciardiello, Fortunato; Orditura, Michele (Frontiers in Oncology, 2019)
Objective: We assessed the genomic profile of four representative BRCA-mutated ovarian cancer (OC) patients treated with olaparib to investigate the relationship between intratumor heterogeneity and response to olaparib treatment. The main aim is to identify possible predictive biomarkers of response to olaparib through the analysis of HRD or not HRD genes and the definition of BRCA1 promoter methylation status. Methods: DNA, isolated from formalin-fixed, paraffin-embedded (FFPE) diagnostic OC tissues, was analyzed by FoundationOneCDx™. This assay detects alterations in a total panel of 324 genes, using the Illumina® HiSeq 4000 platform. Methylation analysis of the BRCA gene promoter was carried out by pyrosequencing with PyroMark Q24 platform (Qiagen), an in vitro nucleic acid sequence-based detection test based on pyrosequencing technology for quantitative measurements of methylation status. Results: Case #1 and #2 were defined Long-term responders since they received olaparib for 27 and 36 months, respectively. These remarkable results could be explained, at least in part, by the presence of somatic IDH1 mutation in case #1 and PI3K and SOX2 amplification in the case #2. In case #3, the somatic NF1 mutation appeared to be related to the short duration of response. In the case #4, in which the patients is on olaparib from 1 year achieving a stable disease, a somatic mutation of BRCA1 was recorded. Moreover, in all cases, levels of BRCA1 promoter were strictly related to olaparib response. Conclusions: Based on our experience, genomic analysis of tumor tissue at diagnosis might help to determine the future response to olaparib in advanced OC setting, revealing predictive biomarkers beyond BRCA 1-2 and HRD status.